Factors Associated with the Incidence of Post-Disaster Stunting in Toddlers Aged 25-59 Months in Posyandu Biromaru Health Centre Working Area - Wandira, Bertin Ayu; Hermiyanty; Suwendro, Novi Inriyanny; Rakhman, Aulia (Media Publikasi Cendekia Indonesia, 2023)
Stunting is a major problem in Central Sulawesi Province, with Sigi District having the highest prevalence at 40.7%. Stunting is a condition where children under five years of age fail to thrive due to chronic malnutrition, resulting in stunted growth. This condition hinders human development and has a negative impact on the future. The study aimed to identify the factors related to post-disaster stunting in toddlers aged 25-59 months in the Biromaru Health Centre working area. The research design used a quantitative approach with a case-control design, with a sample size of 150 mothers who had babies aged 25-59 months. The results showed that the mother's education level was significantly associated with the incidence of stunting, with mothers who have a low level of education being 2.82 times more likely to have stunted children than mothers with a high level of education. Other factors, such as maternal height, family income, exclusive breastfeeding history, birth weight, gender, and access to health services, did not show a significant relationship with stunting. The study suggests that improving maternal education levels may help reduce the incidence of stunting in toddlers, highlighting the importance of education in preventing child malnutrition.